2008
DOI: 10.1002/asna.200711001
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature primordial gas in merging halos

Abstract: Thermal regime of the baryons behind shock waves arising in the process of virialization of dark matter halos is governed at cetrain conditions by radiation of HD lines. A small fraction of the shocked gas can cool down to the temperature of the cosmic microwave background (CMB). We estimate an upper limit for this fraction: at z = 10 it increases sharply from about q T ∼ 10 −3 for dark halos of M = 5 × 10 7 M⊙ to ∼ 0.1 for halos with M = 10 8 M⊙. Further increase of the halo mass does not lead however to a si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…But here we have also demonstrated, for the first time, that even very low mass halos (M ∼ 10 6 M ), because of the presence of a 10 7 M halo, can be perturbed enough to produce turbulence and shocks inside themselves, thus triggering more efficient cooling than without the merging process. The previous fact does not contradict the results of Shchekinov & Vasiliev (2006) and Vasiliev & Shchekinov (2008) whom by one dimensional simulations shown that in order to ionize the primordial gas in a halo merger process, the halo mass should be > ∼ 10 7 M . Despite in our case the merged halos have masses ∼ 10 6 M , they are accelerated by a ∼ 10 7 M halo and they can reach enough velocity to produce the gas ionization.…”
Section: Discussionmentioning
confidence: 62%
“…But here we have also demonstrated, for the first time, that even very low mass halos (M ∼ 10 6 M ), because of the presence of a 10 7 M halo, can be perturbed enough to produce turbulence and shocks inside themselves, thus triggering more efficient cooling than without the merging process. The previous fact does not contradict the results of Shchekinov & Vasiliev (2006) and Vasiliev & Shchekinov (2008) whom by one dimensional simulations shown that in order to ionize the primordial gas in a halo merger process, the halo mass should be > ∼ 10 7 M . Despite in our case the merged halos have masses ∼ 10 6 M , they are accelerated by a ∼ 10 7 M halo and they can reach enough velocity to produce the gas ionization.…”
Section: Discussionmentioning
confidence: 62%